2014
DOI: 10.3390/ma7075012
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating of Oxide Powders: A New Synthesis Method to Process Biomedical Grade Nano-Composites

Abstract: Composite and nanocomposite ceramics have achieved special interest in recent years when used for biomedical applications. They have demonstrated, in some cases, increased performance, reliability, and stability in vivo, with respect to pure monolithic ceramics. Current research aims at developing new compositions and architectures to further increase their properties. However, the ability to tailor the microstructure requires the careful control of all steps of manufacturing, from the synthesis of composite n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…While the current standard in bioinert ceramics is BIOLOX ® delta (CeramTec, Plochingen, Germany), its position may eventually be challenged by other ZrO 2 and ZTA compositions having both high strength and little or no LTD, or by non-oxide ceramics such as Si 3 N 4 with elevated strength and no LTD. As an example of an improved ZrO 2 , Matsui et al demonstrated that addition of a small amount of germanium oxide (0.30 mol%) to a 3 mol% Y 2 O 3 -doped ZrO 2 coupled with low-temperature sintering produced a fully dense nano-crystalline Y-TZP (grains <300 nm) which exhibited no LTD for 4 years in a steam autoclave at 140 • C [572]. As other examples, ZTA nano-composites which exclude the use of yttria, or which incorporate zirconia nano-particles (<500 nm) evenly dispersed within alumina grains have been developed [154,573]. Both composites result in high strength, tough, and highly LTD resistant ceramics.…”
Section: Bioinert Ceramicsmentioning
confidence: 98%
“…While the current standard in bioinert ceramics is BIOLOX ® delta (CeramTec, Plochingen, Germany), its position may eventually be challenged by other ZrO 2 and ZTA compositions having both high strength and little or no LTD, or by non-oxide ceramics such as Si 3 N 4 with elevated strength and no LTD. As an example of an improved ZrO 2 , Matsui et al demonstrated that addition of a small amount of germanium oxide (0.30 mol%) to a 3 mol% Y 2 O 3 -doped ZrO 2 coupled with low-temperature sintering produced a fully dense nano-crystalline Y-TZP (grains <300 nm) which exhibited no LTD for 4 years in a steam autoclave at 140 • C [572]. As other examples, ZTA nano-composites which exclude the use of yttria, or which incorporate zirconia nano-particles (<500 nm) evenly dispersed within alumina grains have been developed [154,573]. Both composites result in high strength, tough, and highly LTD resistant ceramics.…”
Section: Bioinert Ceramicsmentioning
confidence: 98%
“…16 As reported, zirconia is a biocompatible material with great mechanical properties. 17 Our previous works reported the similar bioactivity of NANOZR, Y-TZP and CpTi after being polished. 18 However, the mechanisms of osteoblast adhesion onto zirconia material needed further investigation.…”
Section: Discussionmentioning
confidence: 71%
“…Besides the method investigated by Schehl et al [ 153 ], based on the use of organic precursors, also inorganic salts were used to coat the surface of commercial Al 2 O 3 particles and to induce the crystallization of second-phases upon calcination. Yuan et al [ 156 ], for instance, added cerium and aluminum nitrates to the isopropanol suspension of ZrO 2 powder, in order to obtain ceria-stabilized ZrO 2 /2 wt. %Al 2 O 3 composites.…”
Section: Synthesis Of Nanocomposite Ceramic Powdersmentioning
confidence: 99%